ERRORS AND CAUSES OF INEFFECTIVENESS OF PRIMARY OPERATIONS FOR PHLEGMONS OF THE FACE AND NECK - Okhunov, A.O.; Boboev, K.Kh.; Bobokhodjaev, A.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. To date, surgical intervention on the primary purulent focus remains fundamental in the overall treatment program for purulent surgical patients with any localization of the inflammatory process. However, the operation on the primary purulent focus is not always radical and there may be a need for a second operation. Material. A study of clinical manifestations and the state of homeostasis in 117 patients with phlegmons of the maxillofacial region and neck of odontogenic origin, operated repeatedly, was carried out. The studies were conducted on the clinical basis of the Department of Maxillofacial Surgery of the Tashkent State Dental Institute. Conclusion. The main reasons for the ineffectiveness of primary operations for phlegmons of the face and neck are errors in nosological and topical diagnostics, the discrepancy between the volume of surgical intervention and the localization and prevalence of the inflammatory process, the nature of the inflammatory reaction and the imbalance of general therapy depending on the form of purulent infection. Indications for repeated surgery are determined by an increase in the intensity and expansion of the range of local and general complaints, a low detoxifying effect of previous surgical intervention, increased signs of a local inflammatory reaction and negative dynamics of paraclinical indicators.